Accessibility of Voters with Disabilities in General Elections - Fitriyah, Fitriyah; Herawati, Nunik Retno (JURNAL ILMU SOSIAL, 2021)
Discrimination to voters with disabilities occurs recurrently although many efforts are taken to break such discrimination through regulations. This study intends to specifically describe the accessibility of voters with disabilities in the 2019 election, the obstacles, and recommendation for policy designs to improve the accessibility of voters with disabilities in elections. The simultaneous elections of 2019 which involve the legislative and presidential elections contribute to the complexity of the election, especially for the voters with disabilities. The qualitative research approach applies the analytical descriptive method. The data collection used literature studies on regulations, research results and articles related to disability. Primary data were obtained from interviews and observations (March-April 2019) in the city of Semarang. The data were also collected from documentary studies and online news searches regarding the policies/programs/activities of the General Election Commission (KPU), the General Election Supervisory Agency (Bawaslu) and organizations of disabilities, including using excerpts from their statements. The results of this study conclude that during the 2019 General Election KPU has not been able to remove social barriers to the fulfillment of the rights of disabled voters. The findings show that there is still discrimination for voters with disabilities in the 2019 elections which strengthens the findings of previous researches, although the regulatory aspect is better. The KPU policy of providing polling station (TPS) Akses at all polling stations is actually not effective in meeting their needs based on the types of disability. There are limitations on the budget and the availability to follow the topographic requirements of TPS Akses. As a recommendation, the quality of service needs to be improved by maximizing the accuracy of data for voters with disabilities, using the data as the basis for procurement and distribution of logistics and the establishment of TPS Akses, and as well as institutionalizing the synergy between KPU, local governments, and disabled community organizations/activists.